Multipath Reliable Routing Using Cluster Based Communication - et. al., Dr. Shanti Rathore, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research we proposed the protection in ANT Optimized primarily based multipath congestion routing performance. Here the situation of DDoS is simulated and examines their impact in dynamic network. The multipath protocol like AOMDV is balance the all load by way of offering alternative path however not knowledgeable at each and every condition. The DDoS attacker is blocking off the whole viable direction in community by way of flooding large quantity of redundant packets in dynamic network. The attacker is that the intermediate node and this attacker contamination is continuously dispersing infection and the entire network overall performance is dumped. The proposed security scheme is identified attacker and their loss effect. Attacker is utterly disabled by way of proposed protection mechanism and their loss is also evaluated. The proposed approach is now not only detecting but also stop community from DDoS attack. The overall performance of protection scheme and assault is measured in three distinctive scenarios of a range of node densities. The proposed scheme is offers attacker free routing and get better network performance after making use of it. The performance of ANT OPTIMIZED is almost equal. The packets receiving, throughput, and PDR are bettering but the loss of packets and unnecessary flooding is decreased in dynamic network.